MORPHOFUNCTIONAL STATE OF THE WALL OF BRONCHI AND LUNG TISSUE STRUCTURES OF DIFFERENT CALIBER IN EXPERIMENTAL BRONCHOECTASIS - Farida Muinovna, Khamidova; Mavlyuda Baxtiyor qizi, Zhovliyeva; Kuvandik Nematovich, Urakov (PT. Antis International Publisher, 2024)
Objective: This study aims to investigate the structural and functional changes in the bronchial wall and lung tissue induced by experimental bronchiectasis in a rabbit model. Method: A total of 34 adult rabbits weighing 2-2.5 kg were subjected to bronchiectasis induction using a modified method involving the insertion of a sterile Capron thread into the tracheal cavity. The rabbits were examined at intervals of 3 to 6 months post-induction, with histological and morphometric analyses conducted on their respiratory tissues. Results: Significant findings included the presence of purulent-mucous exudate, thickening of the bronchial mucosa, and inflammatory infiltrates comprising lymphocytes, neutrophils, and histiocytes. The thickness of the bronchial walls and changes in lung tissue, including emphysema and atelectasis, were also observed, indicating progressive disease over the study period. Morphometric analysis showed a marked increase in the number of cells in the bronchi and lung tissues at 3, 4, and 5 months. Novelty: This study contributes new insights into the pathological progression of bronchiectasis in an animal model, demonstrating the dynamic changes in bronchial structure and inflammatory responses over time, which may have implications for understanding the disease in human populations.